1967
DOI: 10.3758/bf03331623
|View full text |Cite
|
Sign up to set email alerts
|

Open-field behavior in mice: Analysis of maternal effects by means of ovarian transplantation

Abstract: Ovaries from donors of each of two inbred strains (BALBI cJ and CS7BL/6J)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
2
0
0
Order By: Relevance
“…The present study offers little evidence for a maternal influence on the behavior of wild and domestic Norway rats in a novel environment. This result is in agreement with Broadhurst (1961) and Defries et al (1967) who likewise concluded that the prenatal and postnatal maternal environments account for a relatively small proportion of the total variance in open-field activity and defecation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study offers little evidence for a maternal influence on the behavior of wild and domestic Norway rats in a novel environment. This result is in agreement with Broadhurst (1961) and Defries et al (1967) who likewise concluded that the prenatal and postnatal maternal environments account for a relatively small proportion of the total variance in open-field activity and defecation.…”
Section: Discussionsupporting
confidence: 92%
“…In general, the environmental contributions of maternal genotype had little or no effect on offspring emotionality. Defries, Thomas, Hegmann, and Weir (1967) confirmed this result by means of ovarian transplantation in 2 inbred strains of mice. Griesel (1964) reported that rats reared by inactive or active foster mothers exhibited no differences in open-field ambulation and defecation.…”
supporting
confidence: 69%